Democratic Republic of the Congo : Joint Staff Assessment of the Interim Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report, 2003)
Owing to delay in publishing Poverty Reduction Strategy Process Paper (PRSP), the authorities drafted a preparation status report (PSR) on the first year of implementation of the interim poverty reduction strategy paper. The summary of strengthened institutional framework is also included in this study. The IMF staff agrees with the risks set forth in the PSR, which could delay the completion of the PRSP, particularly resurgence, insufficient understanding and internalization of the PRSP process, and delays in the provision of external financial and technical support.